Development and application of a multimetal multibiotic ligand model for assessing aquatic toxicity of metal mixtures. (9th March 2015) - Santore, Robert C.; Ryan, Adam C.
Abstract: A multimetal, multiple binding site version of the biotic ligand model (mBLM) has been developed for predicting and explaining the bioavailability and toxicity of mixtures of metals to aquatic organisms. The mBLM was constructed by combining information from single‐metal BLMs to preserve compatibility between the single‐metal and multiple‐metal approaches. The toxicities from individual metals were predicted by assuming additivity of the individual responses. Mixture toxicity was predicted based on both dissolved metal and mBLM‐normalized bioavailable metal. Comparison of the 2 prediction methods indicates that metal mixtures frequently appear to have greater toxicity than an additive estimation of individual effects on a dissolved metal basis. However, on an mBLM‐normalized basis, mixtures of metals appear to be additive or less than additive. This difference results from interactions between metals and ligands in solutions including natural organic matter, processes that are accounted for in the mBLM. As part of the mBLM approach, a technique for considering variability was developed to calculate confidence bounds (called response envelopes) around the central concentration–response relationship. Predictions using the mBLM and response envelope were compared with observed toxicity for a number of invertebrate and fish species. The results show that the mBLM is a useful tool for considering bioavailability when assessing the toxicity of metal mixtures. Environ Toxicol Chem 2015;34:777–787. © 2014 SETAC